Information technology and the criminal justice system - Pattavina, April (Sage Publications, 2005)
Information technology and the criminal justice system : an historical overview / Terence Dunworth -- Acquiring, implementing, and evaluating information technology / Lois M. Davis and Brian A. Jackson -- How criminal justice agencies use the internet / Roberta E. Griffith -- The internet as a conduit for criminal activity / David S. Wall -- The impact of information technology on crime reporting : the NIBRS system / Donald Faggiani and David Hirschel -- Information technology and crime analysis / Phyllis Parshall McDonald -- Geographic information systems and crime mapping in criminal justice agencies / April Pattavina -- Comprehensive planning of criminal justice information and intelligence systems : ATF's experience in implementing firearms tracing in the United States / Glenn Pierce and Roberta E. Griffith -- Offender-based information sharing : using a consent-driven system to promote integrated service delivery / Kathleen R. Snavely, Faye S. Taxman, and Stuart Gordon -- Environment, technology, and organizational change : notes from the police world / Peter K. Manning -- Information, technology, and criminal justice education / James M. Byrne and Eve Buzawa -- The future of information technology in criminal justice : prospects and challenges / April Pattavina